Partisipasi Politik Masyarakat Dalam Pelaksanaan Pilkada Serentak Di Kota Ternate Provinsi Maluku Utara Tahun 2018 (Studi Kasus Di Kecamatan Ternate Selatan) - Mukhti Arif; Mulyana Mulyana (Jurnal Ilmu Pemerintahan Widya Praja, 2020)
This research focuses on the problem that there are still people who are registered as permanent voters but have not used their voting rights. The purpose of this study is to determine the level of public political participation in the 2018 Concurrent Regional Head Elections, inhibiting and supporting factors for community political participation and the efforts that have been made to increase public political participation in the 2018 Concurrent Regional Head Elections. This research uses qualitative research methods with descriptive approach. The results of the study show that the Political Participation of the Community in the 2018 Concurrent Regional Head Elections in South Ternate District is still lacking, seen from the number of people who do not exercise their voting rights. This condition is due to the lack of understanding and awareness of the public to participate in the Pilkada. In compiling the voter list, public participation is still lacking because it is difficult to find at the time of data collection, then in campaign activities, community participation is also still lacking because many choose to work instead of coming to the campaign as well as community participation in voting which is still lacking and does not reach the KPU target. . The inhibiting factors for community political participation in Pilkada are social status and economic status. The supporting factors for community political participation in the Pilkada are the political affiliation of parents and organizational experience. Efforts have been made to increase political participation through formal and informal socialization activities. The suggestions conveyed, namely that all organizers of the Regional Head Election simultaneously carry out socialization, by increasing communication and coordination between the KPU and the Regional Government so that socialization is carried out as well as sustainable political education, the committee recruitment process is in accordance with integrity and expertise.